SUMBER DAYA INSANI DALAM MENINGKATKAN KUALITAS PELAYANAN - Sukma Fitri, Mizani; Rahman, Abd.; Jufri, Muhammad (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
Human Resource Development, the potential to carry out an effort to improve and increase employee competence and performance which is one source of competitive advantage as the main and important key element in order to achieve success in competing and achieving goals. Service quality is one of the main tools for achieving the success of a company. Quality service is the existence of a service system that is oriented to the interests of customers or service users. This type of research is field research with qualitative descriptive methods. This research uses two types of data sources, namely primary data and secondary data. The data collection techniques use interview, observation and documentation techniques. From the research results, it can be seen that the analysis of human resource development strategies in improving the quality of service at Supermarket 1 Assyarif is to carry out Human Resources Management, Recruitment, Motivation, Development and Training, Maintaining Relationships and Work Atmosphere, Performance Assessment, and Compensation.